2020
DOI: 10.1002/14651858.cd011860.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Education and training for preventing and minimizing workplace aggression directed toward healthcare workers

Abstract: Background Workplace aggression constitutes a serious issue for healthcare workers and organizations. Aggression is tied to physical and mental health issues at an individual level, as well as to absenteeism, decreased productivity or quality of work, and high employee turnover rates at an organizational level. To counteract these negative impacts, organizations have used a variety of interventions, including education and training, to provide workers with the knowledge and skills needed to prevent aggression.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
115
0
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(130 citation statements)
references
References 114 publications
5
115
0
10
Order By: Relevance
“…Workplace violence can lead to adverse effects on organizations and on the physical and mental health of their workers (Geoffrion et al, 2020; Liu et al, 2019). Healthcare staff affected by workplace violence suffer physical injuries and negative behavioral, cognitive, and emotional outcomes (Mento et al, 2020; Nowrouzi‐Kia, Isidro, Chai, Usuba, & Chen, 2019).…”
Section: Consequences and Correlates Of Workplace Violencementioning
confidence: 99%
“…Workplace violence can lead to adverse effects on organizations and on the physical and mental health of their workers (Geoffrion et al, 2020; Liu et al, 2019). Healthcare staff affected by workplace violence suffer physical injuries and negative behavioral, cognitive, and emotional outcomes (Mento et al, 2020; Nowrouzi‐Kia, Isidro, Chai, Usuba, & Chen, 2019).…”
Section: Consequences and Correlates Of Workplace Violencementioning
confidence: 99%
“…Multiple databases were searched. The literature search periods were up to June 2020 for the SR by Geoffrian et al 9 ; up to May 2019 for the SR by Spelten et al 6 ; between January 2000 and April 2019 for the SR by Raveel and Schoenmakers 10 ; between January 2009 and December 2017 for the SR by d'Ettore et al 11 ; up to April 2016 for the SR by Weiland et al 12 ; between January 1991 and February 2016 for the SR by Gaynes et al 14 ; and up to December 2015 for the SR by Ramacciati et al 13 The relevant primary studies in these SRs comprised RCTs, non-randomized comparative studies, and pre-and post-studies and the number of relevant primary studies in each SR ranged between 1 and 5. In addition, 1 SR 13 included a review article, and 1 SR 10 included a SR and a review article.…”
Section: Methodsmentioning
confidence: 99%
“…Of these 47 potentially relevant articles, 40 publications were excluded for various reasons, and 7 publications met the inclusion criteria and were included in this report. These comprised 7 systematic reviews (SRs) 6,[9][10][11][12][13][14] No randomized controlled trials (RCTs) or evidence-based guidelines were identified. Appendix 1 presents the PRISMA 15 flow chart of the study selection.…”
Section: Quantity Of Research Availablementioning
confidence: 99%
See 1 more Smart Citation
“…The frequency of traumatic events is not the same in the different categories of workers. Violence and bullying constitute a serious issue in all workplaces, and especially for healthcare workers [21][22][23]. Injuries at work are also common in health care workers, who are particularly prone to needle sticks and biological injuries [24,25].…”
Section: Introductionmentioning
confidence: 99%